+0  
 
0
825
3
avatar

Find the 5th term of the expansion of the binomial (3x-1)7

Guest Mar 1, 2017
 #1
avatar
0

Find the 5th term of the expansion of the binomial (3x-1)7

 

The 5th term =3^3 x binomial(7, 4) x^3 =945 x^3.

Guest Mar 1, 2017
 #2
avatar+87301 
0

The 5th term will be given by :

 

C(7, 4) (3x)^3 * (1)^4  =    35 * 27 * x^3   =  945 x^3

 

 

cool cool cool

CPhill  Mar 1, 2017
 #3
avatar+19639 
+5

Find the 5th term of the expansion of the binomial (3x-1)7

 

\(\begin{array}{|rcll|} \hline (3x-1)^7 &=& \binom{7}{0}\cdot (3x)^7 + \binom{7}{1}\cdot (3x)^6\cdot(-1)^1 \\ &+& \binom{7}{2}\cdot (3x)^5\cdot(-1)^2 + \binom{7}{3}\cdot (3x)^4\cdot(-1)^3 \\ &+& \color{Maroon}\binom{7}{4}\cdot (3x)^3\cdot(-1)^4\color{black} + \binom{7}{5}\cdot (3x)^2\cdot(-1)^5 \\ &+& \binom{7}{6}\cdot (3x)^1\cdot(-1)^6 + \binom{7}{7}(-1)^7 \\ \hline \end{array} \)

 

The 5th term of the binomial (3x-1)is:

\(\begin{array}{|rcll|} \hline && \color{Maroon}\binom{7}{4}\cdot (3x)^3\cdot(-1)^4\color{black} \\ &=& \binom{7}{4}\cdot (3x)^3 \quad & | \quad \binom{7}{4} = \binom{7}{7-4} = \binom{7}{3} \\ &=& \binom{7}{3}\cdot (3x)^3 \\ &=& \binom{7}{3}\cdot 27x^3 \\ &=& \frac{7}{3}\cdot\frac{6}{2}\cdot\frac{5}{1}\cdot 27x^3 \\ &=& 7\cdot\frac{6}{6}\cdot 5\cdot 27x^3 \\ &=& 35\cdot 27x^3 \\ &\mathbf{=}& \mathbf{945x^3} \\ \hline \end{array}\)

 

laugh

heureka  Mar 1, 2017

13 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.